PENYULUHAN VITAMIN DAN SUPPLEMEN YANG DIBUTUHKAN TUBUH LANSIA DI KELURAHAN TIDUNG, PULAU SERIBU 17-19 JUNI 2022 - Romauli Lumbantobing; Tjio Ie Wei; Tigor P Simanjuntak; Fransiska Sitompul (JURNAL ComunitÃ Servizio : Jurnal Terkait Kegiatan Pengabdian kepada Masyarakat, terkhusus bidang Teknologi, Kewirausahaan dan Sosial Kemasyarakatan, 2022)
Abstract The COVID-19 (coronavirus) pandemic has caused many changes in daily life. Good nutrition is very important before, during and after infection. Adequate nutrition, especially vitamins and minerals, is needed in maintaining an optimal immune system, vegetables and fruits are the best sources of various vitamins, minerals and fiber. According to the World Health Organization (WHO), the elderly is someone who has entered the age of 60 years and over. In Indonesia, the number of elderly people increased from 18 million people (7.56%) in 2010 to 25.9 million people (9.7%) in 2019 and can be expected to continue to increase where in 2035 to 48.2 million people (15,77%). The elderly need a variety of foods to maintain a nutritional balance, one of which is to avoid infectious diseases (eg infections) and non-communicable diseases (eg hypertension). In principle, the elderly really need protection and the provision of correct information during a pandemic, especially regarding mental and physical health care. According to statistical data, the Thousand Islands Regency in 2021 consists of 2 sub-districts and 6 urban villages. During the period of 1 year (2019 – 2020), the population of the Thousand Islands experienced an increase of 1.56 percent. If we look at the population by age group, it can be seen that the composition of productive age (15-64 years) is almost double the unproductive age (> 64 years/elderly) which is 66.82 percent. Therefore, in community service activities (PKM), we want to do Vitamin and Food Supplement Counseling for the elderly (over 60 years old) in P. Tidung Village, Pulau Seribu on 17-19 June 2022. Keywords: Community Service; Vitamin and Supplement; elderly; The Covid-19 Pandemic.